ACHIEVEMENTS OF THE PLAIN SWEDISH MOVEMENT FROM THE POLISH PERSPECTIVE - HADRYAN, Milena (Comparative Legilinguistics, 2009)
The paper deals with the plain language movement in Sweden from the Polish perspective. Plain Swedish is endorsed by law as an objective of state policy and there is a state body responsible for the quality of public language. The concept of plain language belongs to speech and language planning and is considered to be a central part of Swedish language policy. Polish law only provides protection for the Polish language. As a result, there is neither Polish speech and language planning to promote simple and comprehensible use of official language nor any state body dealing with these issues.